2018
DOI: 10.1097/bpo.0000000000000870
|View full text |Cite
|
Sign up to set email alerts
|

Prognosticating Factors of Relapse in Clubfoot Management by Ponseti Method

Abstract: Level II-prognostic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…Zhao et al. ( 2016 ) also showed that difficulty in correcting the initial deformity was predictive for a relapse. Furthermore, Ponseti et al.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al. ( 2016 ) also showed that difficulty in correcting the initial deformity was predictive for a relapse. Furthermore, Ponseti et al.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic clubfoot or congenital talipes equinovarus (CTEV) is a well-known complex, congenital foot deformity composed of four components, namely: equinus, hindfoot varus, forefoot adduction and cavus 1 . Conservative treatment by manipulating and casting utilised the Ponseti method is the mainstay of practice and satisfactory results have been achieved by several authors 2-6 . The use of a foot abduction brace (FAB) after initial correction is mandatory to maintain the correction and to prevent the recurrence of CTEV 1, 6-9 .…”
Section: Introductionmentioning
confidence: 99%
“…Conservative treatment by manipulating and casting utilised the Ponseti method is the mainstay of practice and satisfactory results have been achieved by several authors 2-6 . The use of a foot abduction brace (FAB) after initial correction is mandatory to maintain the correction and to prevent the recurrence of CTEV 1, 6-9 . However, this is a challenging process, which requires cooperation from the parents or guardians 1, 3, 10, 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations